Microbiological Quality Assessment and Safety of Local Shop Yogurt (Dahi) in Savar Area of Dhaka, Bangladesh (Bioresearch Communications, 2026)
Dahi, or yogurt, is a popular fermented dairy food in Bangladesh. Its broad use emphasizes the significance of ensuring microbiological safety, especially as it is frequently marketed under various storage conditions. Consumers may be at risk if cleanliness and storage standards are lacking. The purpose of this study was to evaluate the microbiological purity and safety of yogurt samples, both refrigerated and non-refrigerated, gathered from 10 different locations in Dhaka's Savar neighborhood. A total of twenty yogurt samples were examined, consisting of ten samples at room temperature and ten samples refrigerated. Microbiological tests were performed in accordance with World Health Organization (WHO) guidelines, with an emphasis on total viable bacterial counts, coliforms, and fungal contamination (including yeast and mold). Total viable bacterial counts in refrigerated samples were between 2.02 × 10⁶ and 2.82 × 10⁶ CFU/ml. Non-refrigerated samples had significantly higher counts, ranging from 3.01 × 10⁶ to 3.87 × 10⁶ CFU/ml. Coliform contamination of up to 10 CFU/ml was found in non-refrigerated samples, which could pose health hazards. Furthermore, fungal contamination (yeast and mold) was substantially greater in non-refrigerated samples. Even in the lack of microbiological requirements established by the Bangladesh Standards and Testing Institution (BSTI), these findings highlight the importance of stricter handling, storage, and hygiene procedures. Adopting Good Manufacturing Practices (GMP) and Good Hygiene Practices (GHP) is necessary to assure the safety and quality of yogurt products in regional markets.Bioresearch Commu. 12(2): 2193-2199, 2026 (January)